Implementation of Standard Operating Procedures for Bellboys Handling Guest Luggage During Check-In at Pangeran Beach Hotel - Syabina Jevada Nurul Hidayah; Vischa Mansyera Pratama (Journal of Multidimensional Management, 2025)
Standard Operating Procedures (SOPs) are essential in ensuring structured, consistent, and high-quality hotel operations. This study aims to analyze the implementation of SOPs by bellboys in handling guest luggage during the check-in process at Pangeran Beach Hotel in Padang, Indonesia. Using a descriptive qualitative approach, data were collected through observations, interviews with hotel staff and guests, and documentation. The findings reveal that bellboys performed seven out of ten SOP components consistently, including greeting guests, unloading luggage, securing items, using luggage trolleys, waiting at appropriate locations, verifying room keys, and escorting guests to their rooms. However, certain procedures, such as inviting guests to recheck their belongings and confirming nothing was left in the vehicle, were often omitted. The study concludes that while SOP implementation is generally effective, some steps require reinforcement through staff training and periodic evaluations. Enhancing SOP compliance can strengthen service consistency, improve guest satisfaction, and reinforce the hotel’s professional image.